Consensus statement: loneliness in older adults, the 21st century social determinant of health?. Issue 8 (11th August 2020) - Prohaska, Thomas; Burholt, Vanessa; Burns, Annette; Golden, Jeannette; Hawkley, Louise; Lawlor, Brian; Leavey, Gerard; Lubben, Jim; O'Sullivan, Roger; Perissinotto, Carla; van Tilburg, Theo; Tully, Mark; et al.
Abstract : Objective: The purpose of this consensus statement is to determine the state of the field of loneliness among older people, highlighting key issues for researchers, policymakers and those designing services and interventions. Methods: In December 2018, an international meeting on loneliness was held in Belfast with leaders from across the USA and Europe. A summary of the conclusions reached at this event is presented following a consensus-building exercise conducted both during this event after each presentation as well as after the event through the drafting, reviewing and agreement of this statement by all authors for over 6 months. Results: This meeting resulted in an agreement to produce a consensus statement on key issues including definitions of loneliness, measurement, antecedents, consequences and interventions. Discussion: There has been an exponential growth in research on loneliness among older adults. However, differing measurements and definitions of loneliness mean the incidence and prevalence, associated risk factors and health consequences are often conflicting or confusing especially for those developing policy and services.